Secondary battery and method for manufacturing secondary battery

By using a positive electrode active material with small volume variation and having a crystalline structure similar to that of CdCl2, the problem of difficult maintenance of lithium ion conductive paths in all-solid lithium ion secondary batteries is solved, and a secondary battery with high capacity and excellent safety is achieved.

CN119674171APending Publication Date: 2025-03-21SEMICON ENERGY LAB CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411885320.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-11-24
Filing Date
2018-11-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the charging and discharging process of all-solid lithium-ion secondary batteries, the volume change of active substances makes it difficult to maintain the conductive paths of lithium ions, resulting in a decrease in capacity.

Method used

The positive electrode active material with small volume changes in the charged and discharged states is used, and has a crystalline structure similar to that of CdCl2 type. The volume and crystalline structure of charge and discharge are small, and the conductive path of lithium ions is maintained.

Benefits of technology

The capacity reduction in the charge and discharge cycle is effectively suppressed, the capacity and safety of all-solid-state lithium-ion secondary batteries are improved, and a high productivity manufacturing method is realized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674171A_ABST
    Figure CN119674171A_ABST
Patent Text Reader

Abstract

In an all-solid-state secondary battery, when the volume of an active material changes due to charging and discharging, it is sometimes difficult to maintain a conductive path. A positive electrode active material having a small change in volume between a charged state and a discharged state is used in an all-solid-state secondary battery. For example, compared with a conventional positive electrode active material, the positive electrode active material has a layered rock salt type crystal structure in a discharge state and has a crystal structure similar to a cadmium chloride type crystal structure in a charged state with a charge depth of about 0.8, and the volume and crystal structure of the positive electrode active material change little by charge and discharge.
Need to check novelty before this filing date? Find Prior Art

Description

This application is a divisional application of a patent application with application number 201880072846.2, application date November 16, 2018, and invention name “Secondary battery and method for manufacturing secondary battery”. Technical Field

[0001] The present invention relates to an article, a method or a manufacturing method. The present invention relates to a process, a machine, a product or a composition of matter. One embodiment of the present invention relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, an electronic device or a manufacturing method thereof. In particular, one embodiment of the present invention relates to a positive electrode active material that can be used for a secondary battery, a secondary battery and an electronic device having a secondary battery.

[0002] Note that the term "power storage device" in this specification refers to any element or device having a power storage function, such as lithium ion secondary batteries (also referred to as secondary batteries), lithium ion capacitors, and electric double layer capacitors.

[0003] Note that the electronic device in this specification refers to any device having a power storage device. An electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all electronic devices. Background Art

[0004] In recent years, the research and development of various power storage devices such as lithium-ion secondary batteries, lithium-ion capacitors and air batteries has become increasingly popular. In particular, with the development of the semiconductor industry such as mobile phones, smart phones, tablet computers and notebook personal computers, portable music players, digital cameras, medical equipment, or new generation clean energy vehicles such as hybrid electric vehicles (HEV), electric vehicles (EV), plug-in hybrid electric vehicles (PHEV), the demand for high-output, high-energy-density lithium-ion secondary batteries has increased dramatically. As a rechargeable energy supply source, lithium-ion secondary batteries have become a necessity in the modern information society.

[0005] In particular, all-solid-state lithium-ion secondary batteries that use solid electrolytes instead of organic electrolytes and lithium salts have attracted attention. All-solid-state lithium-ion secondary batteries use non-flammable solid electrolytes instead of flammable organic electrolytes, so they are highly safe. Another advantage is that they can easily achieve high energy density and large-scale.

[0006] Therefore, in order to realize the practical application of all-solid-state lithium-ion secondary batteries, research on solid electrolytes has been particularly intense (Patent Documents 1 to 3).

[0007] In addition, the crystal structure of lithium cobalt oxide, which is widely used as a positive electrode active material for secondary batteries such as all-solid-state batteries, is being studied in detail (Non-Patent Documents 1 to 3). [Prior technical literature] [Patent Document]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 2010-272344 [Patent Document 2] Japanese Patent Application Publication No. 2011-233246 [Patent Document 1] Japanese Patent Application Publication No. 2008-226463 [Non-patent literature]

[0009] [Non-patent document 1] Toyoki Okumura et al, "Correlation of lithium iondistribution and X-ray absorption near-edge structure in O3-and O2-lithiumcobalt oxides from first-principle calculation", Journal of MaterialsChemistry, 2012, 22, pp.17340-17348 [Non-patent document 2] Motohashi, T. et al., "Electronic phase diagram of the layered cobalt oxide system LixCoO2 (0.0≤x≤1.0)", Physical Review B, 80(16); 165114 [Non-patent document 3] Zhaohui Chen et al., “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12)A1604-A1609 Summary of the invention Technical problem to be solved by the invention

[0010] One of the problems of all-solid-state secondary batteries is that it is difficult to maintain a conductive path for lithium ions when the volume of the active material changes due to charge and discharge.

[0011] In existing secondary batteries using organic electrolytes, the electrolyte enters the voids in the active material layer and becomes a conductive path for lithium ions. Therefore, even if the volume of the active material changes and the size of the voids changes, the conductive path for lithium ions can be maintained without any problems because the electrolyte is liquid.

[0012] However, in all-solid-state secondary batteries, when the volume of the active material changes, the gaps become larger and part of the active material may not be in physical contact with the solid electrolyte, making it difficult to maintain the conductive path of lithium ions. Therefore, the capacity may decrease significantly depending on the number of charge and discharge cycles.

[0013] Therefore, one of the purposes of one embodiment of the present invention is to provide an all-solid-state lithium ion secondary battery in which the capacity reduction in the charge and discharge cycle is suppressed. In addition, one of the purposes of one embodiment of the present invention is to provide an all-solid-state lithium ion secondary battery with high capacity and excellent safety and a method for manufacturing the same. In addition, one of the purposes of one embodiment of the present invention is to provide a method for manufacturing an all-solid-state lithium ion secondary battery with high productivity. In addition, one of the purposes of one embodiment of the present invention is to provide a high-capacity all-solid-state lithium ion secondary battery. In addition, one of the purposes of one embodiment of the present invention is to provide an all-solid-state lithium ion secondary battery with high safety or high reliability.

[0014] Another object of one embodiment of the present invention is to provide a novel substance, an active material, a power storage device, or a method for producing the same.

[0015] Note that the description of these objectives does not prevent the existence of other objectives. In one embodiment of the present invention, it is not necessary to achieve all of the above objectives. Objectives other than the above objectives can be extracted from the description of the specification, drawings, and claims. Solutions to technical problems

[0016] In order to achieve the above-mentioned object, a secondary battery of one embodiment of the present invention uses a positive electrode active material with a small volume change between a charging state and a discharging state. For example, compared with existing positive electrode active materials, a positive electrode active material having a layered rock salt type crystal structure in a discharging state and having a crystal structure similar to a CdCl2 type crystal structure in a charging state with a charging depth of about 0.8, specifically, a charging depth of more than 0.77 and less than 0.84, has a small volume and crystal structure change through charging and discharging.

[0017] One embodiment of the present invention is a secondary battery including a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode, wherein the positive electrode has a crystal structure similar to a CdCl2 type crystal structure.

[0018] In addition, another embodiment of the present invention is a secondary battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode, wherein, when the charging depth of the secondary battery is greater than 0.77 and less than 0.84, when the positive electrode is subjected to powder X-ray analysis using CuKα1 lines, there are analysis peaks at θ=19.30±0.20° and 2θ=45.55±0.10°.

[0019] Furthermore, in the above embodiment, the solid electrolyte layer preferably includes an oxide-based solid electrolyte.

[0020] Furthermore, in the above embodiment, the oxide-based solid electrolyte preferably has a NASICON type crystal structure. Effects of the Invention

[0021] By one method of the present invention, an all-solid-state lithium ion secondary battery in which the capacity reduction in the charge and discharge cycle is suppressed can be provided. In addition, an all-solid-state lithium ion secondary battery with high capacity and excellent safety and a method for manufacturing the same can be provided. In addition, a method for manufacturing an all-solid-state lithium ion secondary battery with high productivity can be provided. In addition, a high-capacity all-solid-state lithium ion secondary battery can be provided. In addition, an all-solid-state lithium ion secondary battery with high safety or high reliability can be provided. In addition, a method of the present invention can provide a novel substance, active material, power storage device or a method for manufacturing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] [ Figure 1 ] is a diagram showing the charge depth and crystal structure of a positive electrode active material according to one embodiment of the present invention. [ Figure 2 ] is a diagram showing the charge depth and crystal structure of a conventional positive electrode active material. [ Figure 3 ] is the XRD pattern calculated based on the crystal structure. FIG. 4 is a diagram showing the crystal structure and magnetic properties of a positive electrode active material used in a secondary battery according to one embodiment of the present invention. [ Fig. 5 ] is a diagram showing the crystal structure and magnetic properties of a conventional positive electrode active material. [ Figure 6 ] is a diagram showing an example of a method for producing a positive electrode active material for a secondary battery according to one embodiment of the present invention. [ Figure 7 ] is a diagram showing another example of a method for producing a positive electrode active material for a secondary battery according to one embodiment of the present invention. [ Fig. 8 ] is a diagram showing an example of a secondary battery according to one embodiment of the present invention. FIG. 9 is a diagram showing an example of a secondary battery according to one embodiment of the present invention. [ Fig.10 ] is a diagram showing an example of a method for manufacturing a solid electrolyte for a secondary battery of one embodiment of the present invention. FIG. 11 is a diagram showing an example of a secondary battery according to one embodiment of the present invention. FIG. 12 is a diagram showing an example of a secondary battery according to one embodiment of the present invention. FIG. 13 is a diagram showing an example of a secondary battery according to one embodiment of the present invention and a method for manufacturing the same. FIG. 14 is a diagram showing an example of a secondary battery according to one embodiment of the present invention and a method for manufacturing the same. FIG. 15 is a diagram showing an example of a small electronic device and a vehicle including a secondary battery according to one embodiment of the present invention. FIG. 16 is a diagram showing an example of a vehicle and a house including a secondary battery according to one embodiment of the present invention. Implementation

[0023] Below, the embodiments of the present invention are described in detail with reference to the accompanying drawings. Note that the present invention is not limited to the following description, and a person skilled in the art can easily understand that the mode and details can be transformed into various forms. In addition, the present invention should not be interpreted as being limited to the following embodiments.

[0024] In this specification, etc., crystal planes and orientations are represented by Miller indices. In crystallography, crystal planes and orientations are represented by numbers with a dash attached. However, in this specification, etc., due to symbol restrictions in patent applications, a minus sign (-) is sometimes attached before a number to represent a crystal plane and orientation instead of attaching a dash to the number. In addition, “[]” is used to represent an individual orientation within a crystal, “<>” is used to represent a collective orientation of all equivalent crystal directions, “()” is used to represent an individual face of a crystal plane, and “{}” is used to represent a collective face with equivalent symmetry. In addition, Serves 10 -10 m.

[0025] In this specification, the surface layer of particles of active material etc. refers to the region from the surface to a depth of about 10 nm. The surface formed by cracks can also be called the surface. The region deeper than the surface layer is called the interior.

[0026] In this specification, etc., the layered rock salt type crystalline structure of the composite oxide containing lithium and transition metal refers to a crystalline structure in which a rock salt type ion arrangement in which cations and anions are alternately arranged is provided, and transition metals and lithium are regularly arranged to form a two-dimensional plane, so that lithium can diffuse in two dimensions. In addition, defects such as vacancies of cations or anions may also exist. Strictly speaking, in the layered rock salt type crystalline structure, the lattice of the rock salt type crystal is sometimes deformed.

[0027] In this specification, etc., the rock salt type crystal structure refers to a structure in which cations and anions are arranged alternately. In addition, there may be vacancies of cations or anions.

[0028] In this specification, etc., a crystalline structure similar to a CdCl2 type crystalline structure refers to a crystalline structure belonging to the space group R-3m, in which, when cobalt is included as a transition metal, cobalt exists in a six-coordinated state with oxygen, cobalt forms a two-dimensional triangular lattice, and Li is randomly included between CoO2 layers. In addition, in a crystalline structure similar to a CdCl2 type crystalline structure, oxygen forms a cubic closest packing structure, and the stacking of oxygen presents a repetitive pattern of three layers such as ABCABC. This crystalline structure similar to a CdCl2 type crystalline structure is similar to lithium nickelate (LiNbO2) charged to a charge depth of 0.94. 0.06 However, it is known that pure lithium cobaltate or layered rock salt-type positive electrode active materials containing a large amount of cobalt generally do not have such a crystal structure.

[0029] In a crystal structure similar to the CdCl2 type crystal structure, the arrangement of cations has a symmetry similar to that of the spinel type, and therefore the crystal structure similar to the CdCl2 type crystal structure can also be called a pseudo-spinel type crystal structure.

[0030] The anions of layered rock salt type crystals, the anions of rock salt type crystals and the anions of the crystal structures similar to CdCl2 type crystal structures respectively form cubic close packing structures (face-centered cubic lattice structures). When these crystals are in contact, there is a crystal face with the same orientation of the cubic close packing structure formed by the anions. However, the space group of layered rock salt type crystals and the crystals similar to CdCl2 type crystals is R-3m, which is different from the space group Fm-3m of general rock salt type crystals and the space group Fd-3m of rock salt type crystals with the simplest symmetry, so the Miller index of the crystal face that satisfies the above conditions of layered rock salt type crystals and the crystals similar to CdCl2 type crystals is different from that of rock salt type crystals. In this specification, sometimes the state of the same orientation of the cubic close packing structure formed by the anions in layered rock salt type crystals, the crystals similar to CdCl2 type crystals and the rock salt type crystals refers to the state of roughly consistent crystal orientation.

[0031] It can be judged whether the crystal orientation of the two regions is roughly consistent based on transmission electron microscope (TEM) images, scanning transmission electron microscope (STEM) images, high angle annular dark field-scanning transmission electron microscope (HAADF-STEM) images, annular bright field scanning transmission electron microscope (ABF-STEM) images, etc. X-ray diffraction (XRD), electron diffraction, neutron diffraction, etc. can be used for judgment. In TEM images, the arrangement of cations and anions is observed as the repetition of bright lines and dark lines. When the orientation of the cubic close-packed structure of layered rock salt type crystals and rock salt type crystals is aligned, it can be observed that the angle between the repetition of bright lines and dark lines in the layered rock salt type crystals and the repetition of bright lines and dark lines in the rock salt type crystals is less than 5 degrees and more preferably less than 2.5 degrees. Note that in TEM images, light elements such as oxygen and fluorine cannot sometimes be clearly observed. However, in this case, the consistency of orientation can be judged based on the arrangement of metal elements.

[0032] In this specification, etc., the theoretical capacity of the positive electrode active material refers to the amount of electricity obtained when all the lithium that can be embedded and detached in the positive electrode active material is detached. For example, the theoretical capacity of LiCoO2 is 274mAh / g, the theoretical capacity of LiNiO2 is 274mAh / g, and the theoretical capacity of LiMn2O4 is 148mAh / g.

[0033] In this specification and the like, the depth of charge obtained when all the lithium that can be absorbed and desorbed in the positive electrode active material is absorbed is 0, and the depth of charge obtained when all the lithium that can be absorbed and desorbed in the positive electrode active material is desorbed is 1.

[0034] In this specification, etc., charging refers to the movement of lithium ions from the positive electrode to the negative electrode in the battery and the movement of electrons from the negative electrode to the positive electrode in the external circuit. Charging of the positive electrode active material refers to the detachment of lithium ions. A positive electrode active material having a charging depth of greater than 0.74 and less than 0.9, more specifically a charging depth of greater than 0.77 and less than 0.84, is referred to as a positive electrode active material charged by a high voltage. Therefore, for example, LiCoO2 charged to more than 212mAh / g is a positive electrode active material charged by a high voltage. In addition, the following LiCoO2 is also referred to as a positive electrode active material charged by a high voltage: LiCoO2 that is charged at a constant current of greater than 4.55V and less than 4.63V (when lithium is used as the counter electrode) at a temperature of 25°C, and then charged at a constant voltage until the current value reaches 0.01C.

[0035] Similarly, discharge refers to the movement of lithium ions from the negative electrode to the positive electrode in the battery and the movement of electrons from the positive electrode to the negative electrode in the external circuit. The discharge of the positive electrode active material refers to the insertion of lithium ions. A positive electrode active material with a charge depth of less than 0.06 or a positive electrode active material that discharges more than 90% of the charge capacity from a high voltage charged state is called a fully discharged positive electrode active material. For example, LiCoO2 with a charge capacity of more than 212mAh / g is a positive electrode active material charged by a high voltage, and a positive electrode active material after discharging more than 190.8mAh / g, which is 90% of the charge capacity, is a fully discharged positive electrode active material. In addition, LiCoO2 that is subjected to constant current discharge at a temperature of 25°C until the battery voltage becomes less than 3V (when lithium is used as the counter electrode) is also called a fully discharged positive electrode active material.

[0036] In this specification, etc., non-equilibrium phase transition refers to a phenomenon that causes a nonlinear change in a physical quantity. For example, a non-equilibrium phase transition may occur near the peak of a dQ / dV curve obtained by the differential (dQ / dV) of capacitance (Q) and voltage (V), causing a significant change in the crystal structure.

[0037] (Implementation Method 1) In this embodiment, a positive electrode active material 111 that can be used in a secondary battery 100 according to one embodiment of the present invention will be described.

[0038] [Structure of positive electrode active material] First, refer to Figure 1 and Figure 2 The positive electrode active material 111 of the secondary battery 100 used in one embodiment of the present invention and the existing positive electrode active material are described, and then the differences between these materials are described. Here, the existing positive electrode active material is a simple lithium cobalt oxide (LiCoO2), in which elements other than lithium, cobalt, and oxygen are neither added to the interior nor covered on the surface.

[0039] <Existing positive electrode active materials> As described in Non-Patent Documents 1 and 2, the crystal structure of lithium cobalt oxide changes depending on the depth of charge. Figure 2 The typical crystal structure of lithium cobalt oxide is shown.

[0040] like Figure 2 As shown, LiCoO2 with a charge depth of 0 (discharge state) has a crystal structure of space group R-3m, including three CoO2 layers in a unit cell. This crystal structure is sometimes referred to as an O3-type crystal structure. Note that the CoO2 layer has a structure in which six oxygens are coordinated to an octahedral structure of cobalt, and the edge lines are maintained in a shared state on a plane.

[0041] In addition, lithium cobalt oxide having a charge depth of 1 has a crystal structure of space group P-3m1 and includes one CoO2 layer in a unit cell. Therefore, this crystal structure is sometimes referred to as an O1-type crystal structure.

[0042] In addition, lithium cobalt oxide with a charge depth of about 0.88 has a crystalline structure of space group R-3m. This structure can also be regarded as a structure in which CoO2 structures such as P-3m1(O1) and LiCoO2 structures such as R-3m(O3) are alternately stacked. Sometimes this crystalline structure is called H1-3 type crystalline structure. In fact, the number of cobalt atoms in each unit cell of H1-3 type crystalline structure is twice that of cobalt atoms in each unit cell of other structures. However, in Figure 2 In this specification, in order to facilitate comparison with other crystal structures, the c-axis of the H1-3 type crystal structure is 1 / 2 of the unit cell.

[0043] When charging and discharging at a high voltage with a depth of charge of about 0.88 or higher is repeated, the crystal structure of lithium cobalt oxide repeatedly changes between the H1-3 type crystal structure and the R-3m (O3) structure in the discharged state (i.e., non-equilibrium phase transition).

[0044] However, the CoO2 layers of the two crystalline structures mentioned above deviate greatly. Figure 2 As shown by the dotted line and arrow, the CoO2 layer in the H1-3 crystal structure is significantly deviated from the R-3m (O3) structure. Such dynamic structural changes will have an adverse effect on the stability of the crystal structure.

[0045] Furthermore, the volume difference is also large. The volume difference between the H1-3 type crystal structure containing the same number of cobalt atoms and the O3 type crystal structure in the discharged state is 3.5% or more.

[0046] In addition, the structure of the H1-3 type crystal structure in which CoO2 layers are continuously arranged, such as P-3m1(O1), is likely to be unstable.

[0047] As a result, repeated high-voltage charge and discharge gradually collapse the crystal structure of lithium cobalt oxide. The collapsed crystal structure will cause the cycle characteristics to deteriorate. This is because the collapsed crystal structure reduces the number of locations where lithium can exist stably, making it difficult for lithium to be inserted and removed.

[0048] <Positive electrode active material that can be used for a secondary battery according to one embodiment of the present invention> "internal" In contrast, the positive electrode active material 111 according to one embodiment of the present invention has a small difference in volume and crystal structure between a fully discharged state and a high voltage charged state.

[0049] Figure 1The crystalline structure of the positive electrode active material 111 before and after charge and discharge is shown. The positive electrode active material 111 is a composite oxide containing lithium, cobalt, and oxygen. Preferably, in addition to the above elements, the positive electrode active material 111 further contains magnesium. In addition, the positive electrode active material 111 preferably contains halogens such as fluorine and chlorine.

[0050] Figure 1 The crystal structure of the charge depth 0 (discharge state) is Figure 2 On the other hand, the positive electrode active material 111 of one embodiment of the present invention having a charge depth of 0.77 or more and 0.84 or less has the same R-3m(O3). Figure 2 Different crystal structures. In this specification, etc., the crystal structure of the above-mentioned space group R-3m is referred to as a crystal structure similar to the CdCl2 type crystal structure. Although lithium is omitted in the accompanying drawings of the crystal structure similar to the CdCl2 type crystal structure in order to illustrate the symmetry of the cobalt atom and the symmetry of the oxygen atom, in fact, lithium exists between the CoO2 layers in an amount of more than 16 atomic % and less than 23 atomic % relative to cobalt. In both the O3 type crystal structure and the crystal structure similar to the CdCl2 type crystal structure, it is preferred that a small amount of magnesium exists between the CoO2 layers, i.e., at the lithium position. In addition, it is preferred that a small amount of halogen such as fluorine exists irregularly at the oxygen position.

[0051] In the positive electrode active material 111, compared with the conventional LiCoO2, the change in the crystal structure when a large amount of lithium is released during high voltage charging is suppressed. Figure 1 As shown by the middle dotted line, there is almost no deviation of the CoO2 layer in the above crystal structure. In other words, the symmetry of the crystal structure does not change even when multiple lithiums are removed.

[0052] In the positive electrode active material 111, the volume difference per unit cell between the O3 type crystal structure with a charge depth of 0 and the crystal structure similar to the CdCl2 type crystal structure with a charge depth of 0.88 is 2.5% or less, specifically 2.2% or less.

[0053] Thus, the crystalline structure is not easily collapsed by repeated high voltage charge and discharge. Since the symmetry of the crystal does not change, it is easy to maintain the interface with the solid electrolyte. In addition, since the volume change is small, it is easy to maintain physical contact with the solid electrolyte when used in an all-solid-state battery. Therefore, an all-solid-state secondary battery in which the capacity decline in the charge and discharge cycle is suppressed can be realized.

[0054] In each unit cell of a crystal structure similar to the CdCl2 type crystal structure, the coordinates of cobalt and oxygen can be represented by Co(0,0,0.5) and O(0,0,x), respectively (within the range of 0.20≤x≤0.25).

[0055] Magnesium that exists irregularly in small amounts between CoO2 layers (i.e., lithium positions) can suppress the deviation of the CoO2 layer. Thus, by utilizing the magnesium between the CoO2 layers, a crystalline structure similar to the CdCl2 type crystalline structure can be easily obtained. Therefore, it is preferred that magnesium is distributed throughout the particles of the positive electrode active material 111. In order to distribute magnesium throughout the particles, it is preferred to perform a heat treatment in the manufacturing process of the positive electrode active material 111.

[0056] However, too high a heating temperature may increase the possibility of magnesium invading the cobalt site due to cation mixing. Magnesium at the cobalt site does not have the effect of maintaining the R-3m structure. Furthermore, when the heating temperature is too high, cobalt may be reduced to a divalent state or lithium may evaporate.

[0057] Therefore, it is preferred to add a halogen compound such as a fluorine compound to the lithium cobalt oxide before performing a heat treatment for distributing magnesium throughout the particles. By adding the halogen compound, the melting point of the lithium cobalt oxide is lowered. By lowering the melting point, magnesium can be easily distributed throughout the particles at a temperature where cation mixing is not likely to occur.

[0058] Surface Magnesium is preferably distributed throughout the particles of the positive electrode active material 111, and more preferably, the magnesium concentration in the surface of the particles is higher than the average of the entire particles. The surface of the particles is a crystal defect and the lithium concentration on the surface of the particles is lower than the lithium concentration inside the particles because the lithium on the surface is extracted during charging. Therefore, the surface of the particles tends to be unstable and changes in the crystal structure are easy to begin. The higher the magnesium concentration in the surface, the more effectively the changes in the crystal structure can be suppressed.

[0059] In addition, it is preferable that the concentration of halogen such as fluorine in the surface layer of the positive electrode active material 111 is higher than the average concentration of the entire particle.

[0060] Thus, the surface portion of the positive electrode active material 111 preferably has a composition different from that of the interior, that is, the concentration of magnesium and fluorine is higher than that of the interior. The composition preferably has a crystalline structure that is stable at room temperature. Thus, the surface portion may also have a crystalline structure different from that of the interior. For example, at least a portion of the surface portion of the positive electrode active material 111 may have a rock salt type crystalline structure. Note that when the surface portion has a crystalline structure different from that of the interior, the orientation of the crystals of the surface portion and the interior is preferably roughly the same.

[0061] However, in the surface layer where only MgO or only MgO and CoO (II) form a solid solution, it is difficult for lithium to be inserted and removed. Therefore, the surface layer needs to contain at least cobalt and also contain lithium during discharge to have a path for lithium to be inserted and removed. The concentration of cobalt is preferably higher than the concentration of magnesium.

[0062] In addition, the positive electrode active material 111 may also contain a solid electrolyte in the surface portion. As the solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a combination thereof can be used. A solid electrolyte containing aluminum is also stable under high potential conditions, so it is sometimes suitable for use in the surface portion of the positive electrode active material 111.

[0063] In addition, the positive electrode active material 111 may include a buffer layer between the surface layer and the solid electrolyte, and the buffer layer is, for example, lithium niobate. The buffer layer is preferably present between the lithium cobalt oxide and the solid electrolyte.

[0064] Alternatively, the positive electrode active material 111 may include a region where the solid electrolyte or buffer layer described above is mixed with lithium cobalt oxide.

[0065] Crystal Boundary In addition, the magnesium concentration in the crystal grain boundary and its vicinity is preferably higher than that in other regions inside the positive electrode active material 111. The halogen concentration in the crystal grain boundary and its vicinity is preferably higher. In addition, either titanium or aluminum may be contained in the crystal grain boundary and its vicinity.

[0066] Like the particle surface, the crystal grain boundary is also a surface defect, which tends to be unstable and starts to change in the crystal structure. Therefore, the higher the magnesium concentration at the crystal grain boundary and its vicinity, the more effectively the change in the crystal structure can be suppressed.

[0067] Even if cracks are generated along the crystal grain boundaries of the particles of the positive electrode active material 111, the high concentrations of magnesium and halogens at and near the crystal grain boundaries can increase the concentrations of magnesium and halogens near the surface where the cracks are generated. Therefore, the positive electrode active material containing cracks can also have high corrosion resistance to hydrofluoric acid.

[0068] Note that in this specification and the like, the vicinity of a crystal grain boundary refers to a region from the grain boundary to about 10 nm.

[0069] 〈Analysis Method〉 In order to determine whether a certain material is a positive electrode active material 111 of one embodiment of the present invention having a crystal structure similar to a CdCl2 type crystal structure when charged at a high voltage, the positive electrode charged at a high voltage can be analyzed by XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. In particular, XRD is preferred because it has the following advantages: the symmetry of transition metals such as cobalt in the positive electrode active material can be analyzed with high resolution; and the positive electrode obtained by only disassembling a secondary battery can be measured with sufficient accuracy.

[0070] As described above, the volume and crystal structure of the positive electrode active material 111 of one embodiment of the present invention change little between the high voltage charge state and the discharge state. Materials in which more than half of the crystal structures have large changes between the high voltage charge state and the discharge state are not preferred because they cannot withstand high voltage charge and discharge. Sometimes the desired crystal structure cannot be achieved simply by adding impurity elements. For example, the positive electrode active material of lithium cobalt oxide containing magnesium and fluorine sometimes has a crystal structure similar to the CdCl2 type crystal structure of more than 60wt% when charged at a high voltage, and sometimes more than half of the H1-3 type crystal structure. Therefore, in order to determine whether a certain material is the positive electrode active material 111 of one embodiment of the present invention, it is necessary to analyze the crystal structure, for example, by XRD.

[0071] However, sometimes the crystal structure of the positive electrode active material in the charged state or the discharged state changes when exposed to air. For example, sometimes the crystal structure similar to the CdCl2 type crystal structure changes to the H1-3 type crystal structure. Therefore, the sample is preferably processed in an inert atmosphere such as an argon atmosphere.

[0072] 《Charging method》 The high voltage charging of the positive electrode active material 111 of the secondary battery 100 used to determine whether a certain composite oxide is applicable to one embodiment of the present invention is preferably performed on a secondary battery whose counter electrode is lithium metal. This is because when a material other than lithium metal is used as the counter electrode, the potential of the secondary battery is different from the potential of the positive electrode, so it is not easy to measure the positive electrode potential. Unless otherwise specified, the voltage and potential in this specification, etc. refer to the potential of the positive electrode.

[0073] When analyzing an all-solid-state secondary battery using a material other than lithium metal such as graphite, silicon, lithium titanium oxide, etc. as the negative electrode, it is preferred to disassemble the single cell, remove the negative electrode, and then reconstruct the single cell whose counter electrode is lithium. Examples of methods for removing the negative electrode include shearing, scraping, and polishing.

[0074] The secondary battery whose counter electrode is lithium metal is charged at a constant current of 4.6V and 0.5C, and then charged at a constant voltage until the current value becomes 0.01C. Here, 1C is set to 137mA / g and the temperature is set to 25°C. After charging in this way, the coin battery is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode charged with a high voltage. It is preferred that various subsequent analyses are also performed under an argon atmosphere. For example, XRD can be performed on the positive electrode active material enclosed in a sealed container in an argon atmosphere.

[0075] 《XRD》 Figure 3The ideal powder XRD pattern represented by CuKα1 line calculated from the model of the crystal structure similar to the CdCl2 type crystal structure and the H1-3 type crystal structure is shown. For comparison, Figure 3 Also shown are ideal XRD patterns calculated from the crystal structures of LiCoO2(O3) with a charge depth of 0 and CoO2(O1) with a charge depth of 1. Note that the patterns of LiCoO2(O3) and CoO2(O1) were calculated using Reflex PowderDiffraction, one of the modules of Materials Studio (BIOVIA), using crystal structure information obtained from the Inorganic Crystal Structure Database (ICSD). The range of 2θ is 15° to 75°, the step size is 0.01, and the wavelength λ1 is λ2 was not set, and a single monochromator was used. The pattern of the H1-3 type crystal structure was prepared under the above conditions based on the crystal structure information recorded in non-patent document 3. The crystal structure similar to the CdCl2 type crystal structure was inferred from the XRD pattern of the positive electrode active material of one embodiment of the present invention, and the crystal structure was fitted using TOPAS Version 3 (crystal structure analysis software manufactured by Bruker), and the XRD pattern of the crystal structure similar to the CdCl2 type crystal structure was prepared in the same manner as other structures.

[0076] like Figure 3 As shown, a crystalline structure similar to a CdCl2 type crystalline structure has diffraction peaks at 2θ of 19.30±0.20° (above 19.10° and below 19.50°) and 2θ of 45.55±0.10° (above 45.45° and below 45.65°). In more detail, a crystalline structure similar to a CdCl2 type crystalline structure has sharp diffraction peaks at 2θ of 19.30±0.10° (above 19.20° and below 19.40°) and 2θ of 45.55±0.05° (above 45.50° and below 45.60°). However, H1-3 type crystalline structure and CoO2 (P-3m1, O1) do not have peaks at the above positions. Therefore, it can be said that the peaks at 2θ of 19.30±0.20° and 2θ of 45.55±0.10° in the state of high voltage charging are characteristics of the positive electrode active material 111 of one embodiment of the present invention.

[0077] It can be said that the peak position observed by XRD is close to that of the crystal structure with a charge depth of 0 and the crystal structure when charged at a high voltage. More specifically, the position difference of two or more, preferably three or more, of the main diffraction peaks of these crystal structures is preferably less than 2θ=0.7, and more preferably less than 2θ=0.5.

[0078] Although the positive electrode active material 111 of one embodiment of the present invention has a crystalline structure similar to the CdCl2 type crystalline structure when charged with a high voltage, it is not necessary for all particles to have a crystalline structure similar to the CdCl2 type crystalline structure. A portion of the particles may also have other crystalline structures or amorphous structures. Note that when the XRD pattern is subjected to Rietveld analysis, the crystalline structure similar to the CdCl2 type crystalline structure preferably accounts for more than 50wt% of the positive electrode active material, more preferably more than 60wt%, and further preferably more than 66wt%. The positive electrode active material whose crystalline structure similar to the CdCl2 type crystalline structure accounts for more than 50wt%, more preferably more than 60wt%, and further preferably more than 66wt% can have sufficiently excellent cycle characteristics.

[0079] The grain size of the positive electrode active material particles similar to the crystal of CdCl2 is only reduced to about 1 / 10 of the LiCoO2 (O3) in the discharged state. Therefore, even under the same XRD measurement conditions as the positive electrode before charge and discharge, a peak of a crystalline structure similar to the CdCl2 type crystalline structure can be confirmed after high voltage charging. On the other hand, although a part of the pure LiCoO2 may have a structure similar to the crystalline structure similar to the CdCl2 type crystalline structure, its grain size is small and its peak is wide and small. The grain size can be obtained from the half width value of the XRD peak.

[0080] It is preferred that the lattice constant of the c-axis in the layered rock salt type crystal structure of the particles of the positive electrode active material in the discharge state, which can be inferred from the XRD pattern, is small. The lattice constant of the c-axis becomes larger when the position of lithium is replaced by a foreign element or cobalt enters the oxygen 4 coordination position (position A). Therefore, a positive electrode active material with good cycle characteristics can be obtained by forming a composite oxide with a layered rock salt type crystal structure with few defects such as Co3O4 with foreign element substitution and spinel crystal structure; mixing a magnesium source and a halogen source with the composite oxide; and then inserting magnesium into the position of lithium.

[0081] The lattice constant of the c-axis in the crystal structure of the positive electrode active material in the discharged state is preferably The following are more preferably The following is more preferably The lattice constant of the c-axis after annealing is preferably the following.

[0082] In order to make the lattice constant of the c-axis within the above range, it is preferred that the impurities are as small as possible. In particular, it is preferred that the amount of transition metals other than cobalt, manganese, and nickel added is as small as possible. Specifically, it is preferably 3,000 ppm or less, and more preferably 1,500 ppm or less. In addition, it is preferred that there is less cation mixing between lithium and cobalt, manganese, and nickel.

[0083] Note that the features known from the XRD pattern are the features of the internal structure of the positive electrode active material. In positive electrode active materials with a particle size (D50) of about 1 μm to 100 μm, the volume of the surface portion is negligible compared to the interior, so even if the surface portion of the positive electrode active material 111 has a different crystal structure from the interior, there is a possibility that it cannot be reflected in the XRD pattern.

[0084] ESR Here, refer to Figure 4A and Figure 4B and Figure 5A and Figure 5B This article describes how to use ESR to determine the difference between a crystal structure similar to a CdCl2 type crystal structure and other crystal structures. Figure 1 and Figure 4A As shown, in a crystal structure similar to the CdCl2 type crystal structure, cobalt exists in a six-coordinated position with oxygen. Figure 4B As shown, in the oxygen-hexacoordinated cobalt, the 3d orbital splits into e g Track and t 2g Orbital, arranged to avoid the direction of oxygen 2g The energy of the orbital is low. The part of cobalt present in the hexacoordinated position of oxygen is t 2g The diamagnetic Co with buried orbitals 3+ The other part of the cobalt present in the oxygen hexacoordinated position may be paramagnetic Co 2+ or Co 4+ Although Co 2+ and Co 4+ They all contain an unpaired electron, so ESR cannot be used for judgment, but paramagnetic cobalt can become Co according to the valence of the surrounding elements. 2+ or Co 4+ .

[0085] According to existing literature, the positive electrode active material can have a spinel crystal structure in which the surface layer does not contain lithium when it is charged. Figure 5A The spinel crystal structure of Co3O4 is shown.

[0086] When spinel is represented by the general formula A[B2]O4, element A exists at a position where oxygen is tetra-coordinated, and element B exists at a position where oxygen is hexa-coordinated. In this specification, etc., the position where oxygen is tetra-coordinated is sometimes referred to as position A, and the position where oxygen is hexa-coordinated is sometimes referred to as position B.

[0087] In the spinel-type crystal structure of Co3O4, cobalt exists not only at the position B where oxygen is six-coordinated, but also at the position A where oxygen is four-coordinated. Figure 5B As shown, in the cobalt with oxygen tetracoordinates, e g The energy of the orbital is lower than t 2g The energy of the orbital. Therefore, the oxygen four-coordinated Co 2+ 、Co 3+ and Co 4+ All of them contain unpaired electrons, so they are paramagnetic. Therefore, when ESR and other methods are used to analyze that the particles contain a sufficient amount of spinel Co3O4, the oxygen four-coordinated Co3O4 will definitely be detected. 2+ 、Co 3+ or Co 4+ The peak of paramagnetic cobalt.

[0088] However, in the positive electrode active material 111 of one embodiment of the present invention, the peak value of paramagnetic cobalt derived from oxygen tetracoordinate is so small that it cannot be confirmed. This means that, unlike the spinel-type crystal structure, the crystal structure similar to the CdCl2-type crystal structure in this specification does not contain oxygen tetracoordinated cobalt in an amount that can be detected by ESR. That is, compared with the existing positive electrode active materials, the positive electrode active material of one embodiment of the present invention sometimes has a small peak value derived from spinel Co3O4 that can be detected by ESR, etc., or is so small that it cannot be confirmed. Spinel Co3O4 does not contribute to the charge and discharge reaction, so the amount of spinel Co3O4 is preferably as small as possible. According to the ESR analysis results, it can be judged that the positive electrode active material 111 is different from the existing positive electrode active materials.

[0089] XPS The area from the surface to about 2nm to 8nm (generally about 5nm) can be analyzed by X-ray photoelectron spectroscopy (XPS), thereby quantitatively analyzing the concentration of each element in about half of the surface area. By performing narrow scan analysis, the bonding state of the elements can be analyzed. The measurement accuracy of XPS is about ±1 atomic % in many cases. Although it depends on the element, the detection limit is about 1 atomic %.

[0090] When the XPS analysis of the positive electrode active material 111 is performed and the cobalt concentration is set to 1, the relative value of the magnesium concentration is preferably 0.4 or more and 1.5 or less, more preferably 0.45 or more and less than 1.00. In addition, the relative value of the halogen concentration such as fluorine is preferably 0.05 or more and 1.5 or less, more preferably 0.3 or more and 1.00 or less.

[0091] In addition, when the positive electrode active material 111 is analyzed by XPS, it is preferred that the peak value of the bonding energy between fluorine and other elements is 682eV or more and less than 685eV, more preferably about 684.3eV. This bonding energy is different from the bonding energy of LiF (685eV) and the bonding energy of MgF2 (686eV). In other words, the fluorine contained in the positive electrode active material 111 is preferably in a bonding state other than LiF and MgF2.

[0092] In addition, when performing XPS analysis of the positive electrode active material 111, it is preferred that the peak value of the bonding energy between magnesium and other elements is greater than 1302eV and less than 1304eV, and more preferably about 1303eV. This bonding energy is different from the bonding energy (1305eV) of MgF2 and is close to the bonding energy of MgO. In other words, the magnesium contained in the positive electrode active material 111 is preferably in a bonding state other than MgF2.

[0093] EDX In EDX measurement, the measurement of a two-dimensionally scanned area is sometimes called EDX surface analysis. The method of extracting linear region data from EDX surface analysis to measure the atomic concentration distribution in the positive electrode active material particles is sometimes called line analysis.

[0094] By EDX surface analysis (e.g., element mapping), the concentrations of magnesium and fluorine in the interior, surface layer, and near the crystal grain boundaries can be quantitatively analyzed. In addition, by EDX line analysis, the peak values ​​of the concentrations of magnesium and fluorine can be analyzed.

[0095] When performing EDX line analysis of the positive electrode active material 111, the magnesium concentration peak of the surface portion preferably appears in a region from the surface of the positive electrode active material 111 to a depth of 3 nm toward the center, more preferably in a region to a depth of 1 nm, and further preferably in a region to a depth of 0.5 nm.

[0096] The fluorine distribution of the positive electrode active material 111 preferably overlaps with the magnesium distribution. Therefore, when performing EDX line analysis, the fluorine concentration peak of the surface portion preferably appears in the region from the surface of the positive electrode active material 111 to a depth of 3nm toward the center, more preferably in the region to a depth of 1nm, and further preferably in the region to a depth of 0.5nm.

[0097] When performing line analysis or surface analysis of the positive electrode active material 111, the atomic ratio of magnesium to cobalt (Mg / Co) near the crystal grain boundary is preferably 0.020 to 0.50, more preferably 0.025 to 0.30, and even more preferably 0.030 to 0.20.

[0098] 《dQ / dVvsV Curve》 When the positive electrode active material of one embodiment of the present invention is discharged at a low rate of, for example, 0.2C or less after being charged at a high voltage, a characteristic voltage change occurs near the end of the discharge. This change can be clearly observed when at least one peak of dQ / dVvsV calculated from the discharge curve is within a range of a constant voltage lower than the peak value appearing at about 3.9V to 3.5V.

[0099] [Method for forming positive electrode active material] Next, refer to Figure 6 An example of a method for forming the positive electrode active material 111 that can be used in the secondary battery 100 according to one embodiment of the present invention will be described. Figure 7 Other specific examples of the formation method are shown.

[0100] <S11> like Figure 6 As shown in S11 of the embodiment, a halogen source such as fluorine and a magnesium source are prepared as materials for the first mixture. In addition, a lithium source is also prepared.

[0101] As a halogen source, for example, lithium fluoride, magnesium fluoride, etc. can be used. Among them, lithium fluoride has a relatively low melting point of 848°C and is easy to melt in the annealing process described later, so it is preferred. As a halogen source, for example, lithium chloride, magnesium chloride, etc. can be used. As a magnesium source, for example, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. can be used. As a lithium source, for example, lithium fluoride, lithium carbonate, etc. can be used. In other words, lithium fluoride can be used as both a lithium source and a halogen source. In addition, magnesium fluoride can be used as both a halogen source and a magnesium source.

[0102] In this embodiment, lithium fluoride is prepared as a halogen source and a lithium source, and magnesium fluoride is prepared as a halogen source and a magnesium source. Figure 7 S11). When lithium fluoride (LiF) and magnesium fluoride (MgF2) are mixed in a molar ratio of about 65:35, the effect of lowering the melting point becomes the highest. When the ratio of lithium fluoride is high, lithium becomes too much and may cause deterioration of the cycle characteristics. For this reason, the molar ratio of lithium fluoride (LiF) and magnesium fluoride (MgF2) is preferably x:1 (0≤x≤1.9), more preferably x:1 (0.1≤x≤0.5), and further preferably x:1 (near x=0.33). In addition, in this specification, etc., "near" refers to a range greater than 0.9 times its value and less than 1.1 times its value.

[0103] When the subsequent mixing and pulverizing steps are performed by a wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol or isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is preferred to use an aprotic solvent that does not easily react with lithium. In this embodiment, acetone (see Figure 7 of S11).

[0104] <S12> Next, the materials of the first mixture are mixed and crushed ( Figure 6 and Figure 7 S12). Although the mixing can be performed by a dry method or a wet method, the wet method is preferred because it can crush the material into smaller pieces. The mixing can be performed using, for example, a ball mill, a sand mill, etc. When a ball mill is used, for example, zirconium balls are preferably used as the medium. It is preferred that the mixing and crushing steps are fully performed to micronize the first mixture.

[0105] <S13, S14> The mixed and crushed materials are recovered ( Figure 6 and Figure 7 S13) to obtain a first mixture ( Figure 6 and Figure 7 S14).

[0106] For example, the average particle size (D50) of the first mixture is preferably greater than 600 nm and less than 20 μm, and more preferably greater than 1 μm and less than 10 μm. When mixed with a composite oxide containing lithium, a transition metal and oxygen in a subsequent process, the first mixture that is micronized in this way is easier to evenly adhere to the surface of the composite oxide particles. It is preferred that the surface of the composite oxide particles is evenly attached with the first mixture because it is easy to make the surface of the composite oxide particles as a whole contain halogen and magnesium after heating. When there is a region in the surface that does not contain halogen and magnesium, it is not easy for the positive electrode active material to have a crystalline structure similar to the CdCl2 type crystalline structure in the charged state.

[0107] <S21> Then, if Figure 6 As shown in S21 of , a lithium source and a transition metal source are prepared as a material of a composite oxide containing lithium, a transition metal and oxygen.

[0108] As the lithium source, for example, lithium carbonate, lithium fluoride, or the like can be used.

[0109] As the transition metal, at least one of cobalt, manganese, and nickel can be used. Since the oxide containing lithium, transition metal, and oxygen preferably has a layered rock salt type crystal structure, cobalt, manganese, and nickel are preferably mixed in a ratio such that the oxide can have a layered rock salt type crystal structure. In addition, aluminum can also be added to the transition metal within the range that the composite oxide can have a layered rock salt type crystal structure.

[0110] As the transition metal source, oxides of the above transition metals, hydroxides of the above transition metals, etc. can be used. As the cobalt source, for example, cobalt oxide, cobalt hydroxide, etc. can be used. As the manganese source, manganese oxide, manganese hydroxide, etc. can be used. As the nickel source, nickel oxide, nickel hydroxide, etc. can be used. As the aluminum source, aluminum hydroxide, aluminum oxide, etc. can be used.

[0111] S22> Next, the lithium source and the transition metal source are mixed (S22). The mixing can be performed by a dry method or a wet method. For example, a ball mill, a sand mill, etc. can be used for mixing. When a ball mill is used, for example, zirconium balls are preferably used as the medium.

[0112] S23> Next, the materials mixed in the above manner are heated. In order to distinguish it from the subsequent heating process, this process is sometimes referred to as roasting or first heating. The heating is preferably carried out at a temperature of 800°C or more and less than 1100°C, more preferably at a temperature of 900°C or more and less than 1000°C, and further preferably at a temperature of about 950°C. When the temperature is too low, the starting material may decompose and melt insufficiently. On the other hand, when the temperature is too high, defects may occur due to excessive reduction of transition metals, evaporation of lithium, etc. For example, defects such as cobalt having a divalent state may occur.

[0113] The heating time is preferably more than 2 hours and less than 20 hours. Calcination is preferably carried out in an atmosphere with little moisture such as dry air (for example, an atmosphere with a dew point of less than -50°C, preferably less than -100°C). For example, it is preferably heated at 1000°C for 10 hours, with a heating rate of 200°C / h and a flow rate of 10L / min in the dry atmosphere. Then, the heated material is cooled to room temperature. For example, the cooling time from a specified temperature to room temperature is preferably more than 10 hours and less than 50 hours.

[0114] S24, S25> The material calcined in the above manner is recovered (S24) to obtain a composite oxide containing lithium, transition metal and oxygen (S25). Specifically, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium cobalt oxide in which a part of cobalt is replaced by manganese, or nickel-manganese-lithium cobalt oxide is obtained.

[0115] In addition, a pre-synthesized composite oxide containing lithium, transition metal and oxygen (see Figure 7 ). In this case, S21 to S24 may be omitted.

[0116] When using a pre-synthesized composite oxide containing lithium, transition metals and oxygen, it is preferred to use a composite oxide with less impurities. Here, lithium, transition metals (cobalt, nickel, manganese), aluminum and oxygen are used as main components, and elements other than the above main components are regarded as impurities. For example, when performing glow discharge mass spectrometry, the total impurity element concentration is preferably less than 10,000 ppmwt, and more preferably less than 5,000 ppmwt. In particular, the total impurity concentration of transition metals such as titanium and arsenic is preferably less than 3,000 ppm, and more preferably less than 1,500 ppm.

[0117] The composite oxide containing lithium, transition metal and oxygen used in S25 preferably has a layered rock salt type crystal structure with few defects and deformation. For this reason, it is preferred that there are few impurities in the composite oxide. When the composite oxide containing lithium, transition metal and oxygen contains more impurities, the crystal structure is likely to have a large number of defects or deformation.

[0118] <s31> Next, the first mixture and the composite oxide containing lithium, transition metal and oxygen are mixed (S31). The transition metal TM contained in the composite oxide containing lithium, transition metal and oxygen and the magnesium Mg contained in the first mixture Mix1 are mixed. Mix1 The atomic number ratio of is preferably 1:y (0.0005≤y≤0.03), more preferably 1:y (0.001≤y≤0.01), and further preferably about 1:0.005.

[0119] In order not to damage the particles of the composite oxide, the mixing of S31 is preferably carried out under milder conditions than the mixing of S12. The mixing can be carried out by a dry method or a wet method. The mixing can be carried out, for example, by a ball mill, a sand mill, etc. When a ball mill is used, for example, zirconium balls are preferably used as the medium.

[0120] S32, S33> The materials mixed in the above manner are recovered (S32) to obtain a second mixture (S33).

[0121] In this embodiment, a method of adding a mixture of lithium fluoride and magnesium fluoride to lithium cobalt oxide with few impurities is described, but one embodiment of the present invention is not limited thereto. A mixture obtained by adding a magnesium source and a halogen source to the starting material of lithium cobalt oxide and then calcining the mixture can be used instead of the second mixture of S33. In this case, there is no need to separate S11 to S14 and S21 to S25, and a simple and highly productive process is achieved.

[0122] Alternatively, lithium cobalt oxide to which magnesium and fluorine are added in advance may be used. When lithium cobalt oxide to which magnesium and fluorine are added is used, the steps before S32 can be omitted, so the steps can be simplified.

[0123] Furthermore, a magnesium source and a halogen source may be added to the lithium cobalt oxide to which magnesium and fluorine have been added in advance.

[0124] <s34> Next, the second mixture is heated. To distinguish it from the previous heating step, this step is sometimes referred to as annealing or second heating.

[0125] Annealing is preferably performed at an appropriate temperature and time. The appropriate temperature and time vary depending on the size and composition of the particles of the composite oxide containing lithium, transition metal and oxygen obtained in S25. When the particles are small, it is sometimes preferred to perform annealing at a lower temperature or for a shorter time than when the particles are large.

[0126] For example, when the average particle size (D50) of S25 particles is about 12 μm, annealing is preferably performed at a temperature of 600° C. to 950° C. Annealing is preferably performed for 3 hours or more, more preferably 10 hours or more, and even more preferably 60 hours or more.

[0127] On the other hand, when the average particle size (D50) of S25 particles is about 5 μm, annealing is preferably performed at a temperature of, for example, 600° C. to 950° C. Annealing is preferably performed for, for example, 1 hour to 10 hours, more preferably about 2 hours.

[0128] The temperature drop time after annealing is preferably, for example, 10 hours to 50 hours.

[0129] It is believed that when the second mixture is annealed, the material with a low melting point in the first mixture (for example, lithium fluoride with a melting point of 848°C) first melts and is distributed in the surface layer of the composite oxide particles. Then, the melted material lowers the melting point of other materials, which may cause other materials to melt. For example, magnesium fluoride (melting point: 1263°C) melts and is distributed in the surface layer of the composite oxide particles.

[0130] Then, the elements contained in the first mixture distributed in the surface layer portion may form a solid solution in the composite oxide containing lithium, a transition metal, and oxygen.

[0131] The elements contained in the first mixture diffuse faster on the surface and grain boundaries than inside the composite oxide particles. Therefore, the concentrations of magnesium and halogen on the surface and grain boundaries are higher than those inside the composite oxide particles. As described later, the higher the magnesium concentration on the surface and grain boundaries, the more effectively the change in the crystal structure can be suppressed.

[0132] <S35> The material annealed in the above manner is recovered to obtain the positive electrode active material 111 of one embodiment of the present invention.

[0133] pass Figure 6 and Figure 7 The method shown can obtain a positive electrode active material having a crystalline structure similar to the CdCl2 type crystalline structure with few defects after high voltage charging. The positive electrode active material having a crystalline structure similar to the CdCl2 type crystalline structure of more than 50% when analyzed by Rietveld analysis has excellent cycle characteristics and rate characteristics.

[0134] When the positive electrode active material contains magnesium and fluorine and is formed by annealing at an appropriate temperature and time, a positive electrode active material having a crystalline structure similar to the CdCl2 type crystalline structure after high voltage charging can be effectively formed. Magnesium and fluorine can also be added to the starting material of the composite oxide. However, when the melting point of the magnesium source and the halogen source is higher than the roasting temperature, the magnesium source and the halogen source added to the starting material of the composite oxide may not melt and cause insufficient diffusion. In this case, the layered rock salt type crystalline structure may have many defects or deformations. As a result, the crystalline structure similar to the CdCl2 type crystalline structure after high voltage charging may also have defects or deformations.

[0135] Therefore, it is preferred to first obtain a composite oxide having a layered rock salt type crystal structure with few impurities, defects or deformations. Then, it is preferred to mix the composite oxide with a magnesium source and a halogen source in a subsequent step and anneal to form a solid solution of magnesium and fluorine in the surface layer of the composite oxide. This method can form a positive electrode active material having a crystal structure similar to a CdCl2 type crystal structure with few defects or deformations after high voltage charging.

[0136] (Implementation Method 2) In this embodiment, materials other than the positive electrode active material 111 described in Embodiment 1 that can be used for the secondary battery 100 of one embodiment of the present invention and the structure of the secondary battery 100 are described.

[0137] Structure of secondary battery> like Fig. 8A As shown, a secondary battery 100 according to one embodiment of the present invention includes a positive electrode 110 , a solid electrolyte layer 120 , and a negative electrode 130 .

[0138] The positive electrode 110 includes a positive electrode current collector 113 and a positive electrode active material layer 114. The positive electrode active material layer 114 includes a positive electrode active material 111 and a solid electrolyte 121. In addition, the positive electrode active material layer 114 may also include a conductive auxiliary agent and a binder.

[0139] The solid electrolyte layer 120 includes a solid electrolyte 121. The solid electrolyte layer 120 is located between the positive electrode 110 and the negative electrode 130, and is a region that does not include the positive electrode active material 111 and the negative electrode active material 131.

[0140] The negative electrode 130 includes a negative electrode current collector 133 and a negative electrode active material layer 134. The negative electrode active material layer 134 includes a negative electrode active material 131 and a solid electrolyte 121. In addition, the negative electrode active material layer 134 may also include a conductive additive and a binder. In addition, when metal lithium is used as the negative electrode 130, Figure 8B As shown, the negative electrode 130 may be one that does not include the solid electrolyte 121. When metal lithium is used as the negative electrode 130, the energy density of the secondary battery 100 can be increased, which is preferable.

[0141] In addition, if Fig.9A As shown, a secondary battery may be used in which a combination of a positive electrode 110, a solid electrolyte layer 120, and a negative electrode 130 is stacked. By stacking a plurality of combinations of a positive electrode 110, a solid electrolyte layer 120, and a negative electrode 130, the voltage of the secondary battery can be increased. Fig.9A This is a schematic diagram of a case where a positive electrode 110, a solid electrolyte layer 120, and a negative electrode 130 are stacked in four layers.

[0142] In addition, the secondary battery 100 of one embodiment of the present invention may also be a thin-film all-solid-state battery. A thin-film all-solid-state battery can be manufactured by depositing a positive electrode, a solid electrolyte, a negative electrode, a wiring electrode, etc. by a gas phase method (vacuum evaporation method, pulsed laser deposition method, gas aeration deposition method, sputtering method). Fig. 9B As shown, the secondary battery 100 can be manufactured by forming a wiring electrode 141 and a wiring electrode 142 on a substrate 140, then forming a positive electrode 110 on the wiring electrode 141, forming a solid electrolyte layer 120 on the positive electrode 110, and forming a negative electrode 130 on the solid electrolyte layer 120 and the wiring electrode 142. As the substrate 140, a ceramic substrate, a glass substrate, a plastic substrate, a metal substrate, etc. can be used.

[0143] <Positive electrode> As the positive electrode active material 111 included in the positive electrode 110, the positive electrode active material 111 described in Embodiment 1 is preferably used. The volume change of the positive electrode active material 111 described in Embodiment 1 due to charge and discharge is reduced, so even if used in an all-solid-state secondary battery, the conductive path of lithium ions can be maintained, which is preferred.

[0144] As the positive electrode current collector 113, materials with high conductivity such as stainless steel, silver, gold, platinum, aluminum, titanium and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, and molybdenum that improve heat resistance are added can also be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. The current collector can appropriately have shapes such as foil, plate (sheet), mesh, punched metal mesh, and drawn metal mesh.

[0145] Alternatively, the positive electrode current collector 113 may be formed by applying a metal paste such as silver paste, gold paste, platinum paste, or metal nano ink, or may be formed by sputtering, CVD, vapor deposition, or the like.

[0146] As the conductive auxiliary agent, a carbon material, a metal material or a conductive ceramic material can be used. In addition, as the conductive auxiliary agent, a fibrous material can also be used. By using the conductive auxiliary agent, a conductive network can be formed in the active material layer. By using the conductive auxiliary agent, the conductive path between the positive electrode active materials can be maintained. By adding the conductive auxiliary agent to the active material layer, an active material layer with high conductivity can be realized.

[0147] As the conductive aid, for example, natural graphite, artificial graphite such as mesophase carbon microbeads, carbon fiber, etc. can be used. As the carbon fiber, for example, carbon fiber such as mesophase pitch carbon fiber, isotropic pitch carbon fiber, etc. can be used. As the carbon fiber, carbon nanofibers or carbon nanotubes can be used. For example, carbon nanotubes can be manufactured by vapor phase growth method, etc. As the conductive aid, for example, carbon materials such as carbon black (acetylene black (AB), etc.), graphite (black lead) particles, graphene or fullerene can be used. In addition, for example, metal powders or metal fibers of copper, nickel, aluminum, silver, gold, etc., conductive ceramic materials, etc. can be used.

[0148] Furthermore, a graphene compound may also be used as a conductive auxiliary agent.

[0149] Graphene compounds sometimes have excellent electrical properties such as high conductivity and excellent physical properties such as high flexibility and high mechanical strength. In addition, graphene compounds have a planar shape. Graphene compounds can form surface contacts with low contact resistance. Graphene compounds sometimes have very high conductivity even if they are thin, so a conductive path can be formed efficiently in a small amount in the active material layer. Therefore, by using a graphene compound as a conductive aid, the contact area between the active material and the conductive aid can be increased, so it is preferred. Preferably, by using a spray drying device, a graphene compound used as a conductive aid for a coating can be formed in a manner that covers the entire surface of the active material. In addition, the resistance can be reduced, so it is preferred. Here, it is particularly preferred that, as a graphene compound, for example, graphene, multilayer graphene or RGO is used. Here, RGO refers to a compound obtained by reducing graphene oxide (graphene oxide: GO), for example.

[0150] When using an active material with a small particle size, for example, an active material with a particle size of less than 1 μm, the specific surface area of ​​the active material is large, so more conductive paths connecting the active materials are required. Therefore, the amount of conductive aid tends to increase, and there is a tendency for the content of active material to decrease relatively. When the content of active material decreases, the capacity of the secondary battery also decreases. In this case, as a conductive aid, since it is not necessary to reduce the content of active material, it is particularly preferred to use a graphene compound that can efficiently form a conductive path even in a small amount.

[0151] As the adhesive, preferably used are rubber materials such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Fluororubber can also be used as the adhesive.

[0152] In addition, as a binder, for example, a water-soluble polymer is preferably used. As a water-soluble polymer, for example, polysaccharides can be used. As polysaccharides, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, starch, etc. can be used. It is more preferred to use these water-soluble polymers and the above-mentioned rubber material in combination.

[0153] Alternatively, as the adhesive, it is preferred to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), ethylene propylene diene monomer polymer, polyvinyl acetate, and nitrocellulose.

[0154] As the binder, a plurality of the above-mentioned materials may be used in combination.

[0155] For example, it is also possible to combine materials with other materials that have a particularly high viscosity regulating function. For example, although rubber materials and the like have high cohesive force and high elasticity, it is sometimes difficult to regulate viscosity when mixed in a solvent. In such a case, for example, it is preferably mixed with a material with a particularly high viscosity regulating function. As a material with a particularly high viscosity regulating function, for example, a water-soluble polymer can be used. In addition, as a water-soluble polymer with a particularly good viscosity regulating function, the above-mentioned polysaccharides can be used, for example, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose and diacetyl cellulose, and regenerated cellulose, and starch can be used.

[0156] Note that cellulose derivatives such as carboxymethyl cellulose, for example, can be easily used as viscosity modifiers by being converted into salts such as sodium salts and ammonium salts of carboxymethyl cellulose to improve their solubility. Due to the increased solubility, the dispersibility of active materials and other components can be improved when forming a slurry for an electrode. In this specification, cellulose and cellulose derivatives used as binders for electrodes include their salts.

[0157] By dissolving a water-soluble polymer in water to stabilize its viscosity, the active material and other materials used as a binder combination, such as styrene-butadiene rubber, can be stably dispersed in an aqueous solution. Since the water-soluble polymer has functional groups, it is expected to be easily and stably attached to the surface of the active material. Most cellulose derivatives such as carboxymethyl cellulose have functional groups such as hydroxyl and carboxyl. Because of the functional groups, the polymer is expected to interact with each other and widely cover the surface of the active material.

[0158] <Negative electrode> As the negative electrode active material 131 included in the negative electrode 130 , for example, lithium metal, alloy-based materials, carbon-based materials, etc. can be used.

[0159] When lithium metal is used for the negative electrode active material 131 , the energy density of the secondary battery is greatly increased, which is preferable.

[0160] As the negative electrode active material, an element that can perform a charge and discharge reaction by alloying / de-alloying reaction with lithium can be used. For example, a material containing at least one of silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The capacity of such an element is larger than that of carbon, and in particular, the theoretical capacity of silicon is large, which is 4200mAh / g. Therefore, silicon is preferably used for the negative electrode active material. In addition, compounds containing these elements can also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb and SbSn can be cited. Elements that can undergo charge and discharge reactions through alloying / de-alloying reactions with lithium, compounds containing the elements, and the like are sometimes referred to as alloy-based materials.

[0161] In this specification, SiO refers to silicon monoxide, for example. Alternatively, SiO may also be represented as SiO x Here, x preferably represents a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0162] As the carbon-based material, graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon nanotube, graphene, carbon black, and the like can be used.

[0163] As graphite, artificial graphite or natural graphite can be cited. As artificial graphite, for example, mesocarbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. can be cited. Here, spherical graphite with a spherical shape can be used as artificial graphite. For example, MCMB sometimes has a spherical shape, so it is preferred. In addition, MCMB is relatively easy to reduce its surface area, so it is sometimes preferred. As natural graphite, for example, flaky graphite, spheroidized natural graphite, etc. can be cited.

[0164] When lithium ions are intercalated in graphite (when lithium-graphite intercalation compounds are generated), graphite shows a potential as low as that of lithium metal (0.05 V or more and 0.3 V or less vs. Li / Li + ). As a result, lithium-ion secondary batteries can show high operating voltages. Graphite also has the following advantages: large capacity per unit volume; relatively small volume expansion; relatively cheap; and higher safety than lithium metal, so it is preferred.

[0165] In addition, as the negative electrode active material, oxides such as titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten oxide (WO2), molybdenum oxide (MoO2), etc.

[0166] In addition, as the negative electrode active material, Li 3N type structure containing lithium and transition metal nitride can be used. 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N3 shows a large charge and discharge capacity (900 mAh / g, 1890 mAh / cm 3 ), so it is preferred.

[0167] When a nitride containing lithium and a transition metal is used as the negative electrode active material, lithium ions are contained in the negative electrode active material, so the negative electrode active material can be combined with a material that does not contain lithium ions, such as V2O5 and Cr3O8, which is used as a positive electrode active material, so it is preferred. Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal can also be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0168] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. Materials that cause conversion reactions can also include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, CoS 0.89 , sulfides such as NiS, CuS, nitrides such as Zn3N2, Cu3N, Ge3N4, phosphides such as NiP2, FeP2, CoP3, fluorides such as FeF3, BiF3.

[0169] In addition, the surface of the negative electrode active material may be covered with a solid electrolyte. For example, an oxide-based solid electrolyte or a sulfide-based solid electrolyte may be used to cover the surface of the negative electrode active material.

[0170] As the conductive aid and the binder which may be contained in the negative electrode active material layer, the same materials as the conductive aid and the binder which may be contained in the positive electrode active material layer can be used.

[0171] As the negative electrode current collector 133, in addition to the same materials as the positive electrode current collector, copper foil, copper plating, etc. can also be used. In addition, as the negative electrode current collector, it is preferable to use a material that does not alloy with carrier ions such as lithium.

[0172] <Solid Electrolyte Layer> As the solid electrolyte 121 included in the solid electrolyte layer 120 , for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a halide-based solid electrolyte, or the like can be used.

[0173] As sulfide solid electrolytes, there are sulfide silicon (Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, etc.); sulfide glass (70Li2S·30P2S5, 30Li2S·26B2S3·44LiI, 63Li2S·38SiS2·1Li3PO4, 57Li2S·38SiS2·5Li4SiO4, 50Li2S·50GeS2, etc.); sulfide crystallized glass (Li7P3S 11 , Li 3.25 P 0.95 S4, etc.) Sulfide solid electrolytes have the following advantages: they are materials with high electrical conductivity; they can be synthesized at low temperatures; they are relatively soft and thus can easily maintain a conductive path even after charge and discharge; etc.

[0174] Examples of oxide-based solid electrolytes include materials having a perovskite-type crystal structure (La 2 / 3- x Li 3x TiO3, etc.); materials with NASICON-type crystal structure (Li 1-X Al X Ti 2-X (PO4)3, etc.); materials with garnet-type crystal structure (Li7La3Zr2O 12 etc.); Materials with LISICON type crystal structure (Li 14 ZnGe4O 16 etc.); LLZO(Li7La3Zr2O 12 ); oxide glass (Li3PO4-Li4SiO4, 50Li4SiO4·50Li3BO3, etc.); oxide crystallized glass (Li 1.07 Al 0.69 Ti 1.46 (PO4)3;Li 1.5 Al 0.5 Ge 1.5 (PO4)3, etc.). Oxide-based solid electrolytes have the advantage of being stable in the atmosphere.

[0175] Examples of halide-based solid electrolytes include LiAlCl4, Li3InBr6, LiF, LiCl, LiBr, LiI, etc. In addition, a composite material in which the above halide-based solid electrolyte is filled in the pores of porous alumina or porous silica can also be used as a solid electrolyte.

[0176] In addition, different solid electrolytes can be mixed and used.

[0177] 《LATP》 Among them, Li 1+x Al x Ti 2-x (PO4)3 (0 < x < 1) (hereinafter, LATP) contains aluminum and titanium, which are elements that can be included in the positive electrode active material 111 of the secondary battery 100 in one embodiment of the present invention. Therefore, a multiplicative effect of improving the cycle characteristics can be expected, so it is preferable. In addition, an improvement in productivity due to shortening of the process can also be expected. In this specification, etc., the NASICON-type crystal structure refers to a compound represented by M2(XO4)3 (M is a transition metal, X is S, P, As, Mo, W, etc.), and refers to a structure in which MO6 octahedra and XO4 tetrahedra share the same vertices and are three-dimensionally arranged.

[0178] Refer to Fig.10 An example of the manufacturing method of LATP will be described.

[0179] 《S51》 First, as materials for LATP, a lithium source, an aluminum source, a titanium source, and a phosphorus source are prepared. In Fig.10 S51, lithium carbonate is used as the lithium source, alumina is used as the aluminum source, titanium oxide is used as the titanium source, and ammonium dihydrogen phosphate is used as the phosphorus source.

[0180] In addition, when performing the next mixing and pulverization steps by a wet method, a solvent is prepared. Aprotic polar solvents are preferably used. In Fig.10 S51, acetone is used as the solvent.

[0181] 《S52》 Next, the above materials are mixed and pulverized ( Fig.10 S52). Although the mixing can be performed by dry method or wet method, the wet method is preferred because it can crush the material into smaller pieces. The mixing can be performed using, for example, a ball mill, a sand mill, etc. When a ball mill is used, for example, zirconium balls are preferably used as the medium. For example, a wet ball mill using zirconium balls is used to perform a ball milling process at 300 rpm for 2 hours.

[0182] 《S53》 Next, the mixed and pulverized materials in the above steps are heated ( Fig.10 S53). In order to distinguish it from the subsequent heating process, this process is sometimes also called pre-baking or first heating. The heating is preferably carried out at a temperature of 170°C or more and less than 500°C, and more preferably at a temperature of 350°C or more and less than 450°C. The heating temperature needs to be higher than the decomposition temperature of the material used as the phosphorus source, but when the heating temperature is too high, there is a concern that titanium oxide is converted into a rutile crystal structure. For example, heating can be carried out at 400°C for 10 hours in a nitrogen atmosphere. The temperature increase can be carried out at 200°C / hour.

[0183] 《S54》 Next, the material heated in the above step is ground using a mortar ( Fig.10 S54).

[0184] 《S55》 Next, the mixture is mixed and crushed using a ball mill, a sand mill, or the like ( Fig.10 S55). Mixing can be performed by a dry method or a wet method. When a wet method is used, a solvent is added. When the mixing and pulverization of this step are fully performed, LATP with less impurities can be synthesized, so it is preferred. For example, a wet ball mill using acetone as a solvent can be used to perform ball milling at 400 rpm for 20 hours.

[0185] 《S56》 Next, the mixed and pulverized materials in the above steps are heated ( Fig.10 S56). In order to distinguish it from the previous heating process, this process is sometimes referred to as main roasting or second heating. The heating is preferably carried out at a temperature of 723°C or more and 1000°C or less, more preferably at a temperature of 800°C or more and less than 950°C. When the temperature is too low, there is a concern that lithium carbonate will not decompose and the synthesis of LATP will be insufficient. On the other hand, when the temperature is too high, there is a concern that lithium will evaporate, etc. For example, heating can be carried out at 900°C for 2 hours in a dry air atmosphere (dew point is below -50°C). The temperature increase can be carried out at 200°C / hour.

[0186] Alternatively, for example, annealing ( Figure 6 and Figure 7 By making the annealing in the manufacturing process of the positive electrode active material 111 also serve as the main calcination in S56, the heating process can be reduced and productivity can be improved.

[0187] 《S57》 Next, the material heated in the above step may be crushed ( Fig.10 S57). The pulverization is performed, for example, by grinding with a mortar and then using a ball mill at 300 rpm for 6 hours. Then, the pulverization may be performed by screening with a sieve having a mesh size of 32 μm.

[0188] Through the above steps, LATP can be obtained.

[0189] <Shape of the outer package and the secondary battery> The outer casing of the secondary battery 100 of one embodiment of the present invention may be made of various materials and shapes, but it is preferable to use an outer casing having a function of pressurizing the positive electrode, the solid electrolyte layer, and the negative electrode.

[0190] For example, FIG. 11A to FIG. 11C An example of a single cell for evaluating materials for an all-solid-state battery is shown.

[0191] Fig.11A 2 is a schematic cross-sectional view of an evaluation cell, which includes a bottom member 261, an upper member 262, and fixing screws and butterfly nuts 264 for fixing them. The evaluation material is fixed by rotating a pressing screw 263 to press the electrode plate 253. An insulator 266 is provided between the bottom member 261 and the upper member 262, which are made of stainless steel. In addition, an O-ring 265 is provided between the upper member 262 and the pressing screw 263 for sealing.

[0192] The evaluation material is placed on the electrode plate 251 , surrounded by an insulating tube 252 , and pressed from above by the electrode plate 253 . Fig. 11B This is a perspective view in which the periphery of the evaluation material is enlarged.

[0193] As the evaluation material, a stack of a positive electrode 250a, a solid electrolyte layer 250b, and a negative electrode 250c is shown. Fig. 11C is its cross-sectional view. Fig.11A , Fig. 11B , Fig. 11C The same symbols are used for the same parts.

[0194] The electrode plate 251 and the bottom member 261 electrically connected to the positive electrode 250a can be said to be equivalent to the positive electrode terminal. The electrode plate 253 and the upper member 262 electrically connected to the negative electrode 250c can be said to be equivalent to the negative electrode terminal. The resistance and the like can be measured while applying pressure to the evaluation material through the electrode plate 251 and the electrode plate 253.

[0195] In addition, the outer package of the secondary battery as one embodiment of the present invention preferably uses a package with excellent airtightness. For example, a ceramic package or a resin package can be used. In addition, when the outer package is sealed, it is preferably shielded from the outside air and carried out in a sealed atmosphere (for example, in a glove box).

[0196] Fig. 12A Shown with FIG. 11A to FIG. 11C A perspective view of a secondary battery according to one embodiment of the present invention having different outer casings and shapes. Fig. 12A The secondary battery includes external electrodes 271 and 272 , which are sealed by an outer package body including a plurality of packaging members.

[0197] Fig. 12B Shown with Fig. 12A An example of a cross section cut by a dot-dash line in FIG. The laminate including the positive electrode 250a, the solid electrolyte layer 250b, and the negative electrode 250c has a structure surrounded and sealed by a packaging member 270a having an electrode layer 273a disposed on a flat plate, a frame-shaped packaging member 270b, and a packaging member 270c having an electrode layer 273b disposed on a flat plate. As the packaging members 270a, 270b, and 270c, insulating materials such as resin materials and ceramics can be used.

[0198] The external electrode 271 is electrically connected to the positive electrode 250a through the electrode layer 273a and is used as a positive electrode terminal. In addition, the external electrode 272 is electrically connected to the negative electrode 250c through the electrode layer 273b and is used as a negative electrode terminal.

[0199] in addition, FIG. 13A to FIG. 14B A laminated secondary battery according to one embodiment of the present invention having a structure different from the above-described structure and an example of its production will be described.

[0200] Fig.13A The appearance diagram of the positive electrode 503 and the negative electrode 506 is shown. The positive electrode 503 includes a positive electrode collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode collector 501. In addition, the positive electrode 503 has a region at its end where a portion of the positive electrode collector 501 is exposed (hereinafter referred to as a tab region). The negative electrode 506 has a negative electrode collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode collector 504. In addition, the negative electrode 506 has a region at its end where a portion of the negative electrode collector 504 is exposed, namely, a tab region. The area or shape of the tab regions of the positive electrode 503 and the negative electrode 506 are not limited to Fig.13A Example shown.

[0201] Next, the negative electrode 506 , the solid electrolyte layer 507 , and the positive electrode 503 are stacked. Fig. 13B The stacked negative electrode 506, solid electrolyte layer 507, and positive electrode 503 are shown. Here, an example using 5 sets of negative electrodes and 4 sets of positive electrodes is shown. Next, the tab regions of the positive electrode 503 are joined to each other, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. As the joining method, ultrasonic welding or the like can be used, for example. Similarly, the tab regions of the negative electrode 506 are joined to each other, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0202] Then, if Fig. 13C As shown in FIG. 1 , a stack of negative electrode 506, solid electrolyte layer 507, and positive electrode 503 is placed on outer package 509, and outer package 509 is folded along the portion indicated by the dotted line. Then, the outer periphery of outer package 509 is bonded. As outer package 509, a laminated film of a laminated metal foil and an organic resin film can be used, for example, aluminum foil or stainless steel foil can be used, and can be bonded by, for example, thermal pressing. By the above steps, a Fig.13D The laminated secondary battery 500 shown in the figure. In addition, although the example of bonding using one laminate film is shown here, two laminate films may be laminated and the edges may be bonded to perform sealing.

[0203] A plurality of laminated secondary batteries 500 may be mounted on an electric vehicle or the like as one battery module.

[0204] Fig.14A 5 is a perspective view showing a state where three laminated secondary batteries 500 are sandwiched and fixed between a first plate 521 and a second plate 524. Fig. 14B As shown, by fixing the distance between the first plate 521 and the second plate 524 using the fixing tools 525 a and 525 b , the three secondary batteries 500 can be pressurized.

[0205] Although Fig.14A and Fig. 14B Although an example using three laminated secondary batteries 500 is shown, the present invention is not limited thereto, and four or more secondary batteries 500 may be used. When ten or more secondary batteries 500 are used, the vehicle can be used as a power source for a small vehicle, and when one hundred or more secondary batteries 500 are used, the vehicle can be used as a large-scale power source for a vehicle. In addition, a protective circuit for preventing overcharging and a temperature sensor for monitoring temperature rise may be provided in the laminated secondary battery 500.

[0206] In an all-solid-state battery, by applying a specified pressure to the stacking direction of the stacked positive or negative electrodes, the contact state of the internal interface can be maintained in a good state. By applying a specified pressure to the stacking direction of the positive or negative electrodes, the expansion in the stacking direction by the charging and discharging of the all-solid-state battery can be suppressed, thereby improving the reliability of the all-solid-state battery.

[0207] This embodiment mode can be used in combination with other embodiment modes as appropriate.

[0208] (Implementation 3) In this embodiment, refer to FIG. 15A to FIG. 16C An example in which the secondary battery described in the above embodiment is mounted in an electronic device will be described.

[0209] [Small electronic devices] First, refer to FIG. 15A to FIG. 15C An example in which the all-solid-state secondary battery according to one embodiment of the present invention is incorporated in a small electronic device will be described.

[0210] Fig.15A An example of a mobile phone is shown. The mobile phone 2100 includes an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like in addition to a display portion 2102 mounted on a housing 2101. In addition, the mobile phone 2100 includes a secondary battery 2107. By using the all-solid-state secondary battery of one embodiment of the present invention as the secondary battery 2107, a mobile phone that is highly safe, lightweight, and has a long service life can be provided.

[0211] The mobile phone 2100 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, network communication, computer games, etc.

[0212] In addition to time setting, the operation button 2103 may have various functions such as power switch, wireless communication switch, silent mode setting and cancellation, power saving mode setting and cancellation, etc. For example, by using the operating system incorporated in the mobile phone 2100, the function of the operation button 2103 can be freely set.

[0213] In addition, the mobile phone 2100 can perform short-distance wireless communication standardized by communication. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0214] In addition, the mobile phone 2100 has an external connection port 2104, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the external connection port 2104. In addition, the charging operation can also be performed using wireless power supply without using the external connection port 2104.

[0215] The mobile phone 2100 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a human body sensor such as a temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, etc. are preferably installed as the sensor.

[0216] Fig. 15B This is a perspective view of a device called a liquid-containing smoking device (electronic cigarette). Fig. 15B In the embodiment, the electronic cigarette 2200 includes a heating element 2201 and a secondary battery 2204 for supplying power to the heating element 2201. When a rod 2202 is inserted therein, the rod 2202 is heated by the heating element 2201. In order to improve safety, a protection circuit for preventing overcharge and overdischarge of the secondary battery 2204 may also be electrically connected to the secondary battery 2204. Fig. 15B The secondary battery 2204 shown includes an external terminal for connecting to a charger. When picking up, the secondary battery 2204 is located at the top, so it is preferably short in total length and light in weight. Since the all-solid-state secondary battery of one embodiment of the present invention is highly safe, has a large capacity, and has excellent cycle characteristics, a small and lightweight electronic cigarette 2200 that can be used for a long period of time can be provided.

[0217] Fig. 15C An unmanned aerial vehicle 2300 including a plurality of rotors 2302 is shown. The unmanned aerial vehicle 2300 includes a secondary battery 2301 of one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely operated via the antenna. Since the all-solid-state secondary battery of one embodiment of the present invention has high safety, large capacity, and excellent cycle characteristics, it is suitable for use as an all-solid-state secondary battery installed in the unmanned aerial vehicle 2300.

[0218] [vehicle] Next, refer to Fig.15D , Fig.15E , FIG. 16A to FIG. 16C An example in which the secondary battery of one embodiment of the present invention is mounted on a vehicle will be described.

[0219] Fig.15D An electric two-wheeled vehicle 2400 using an all-solid-state secondary battery of one embodiment of the present invention is shown. The electric two-wheeled vehicle 2400 includes a secondary battery 2401 of one embodiment of the present invention, a display unit 2402, and a handlebar 2403. The secondary battery 2401 can supply power to the electric motor as a power source. The display unit 2402 can display the remaining power of the secondary battery 2401, the speed or level of the electric two-wheeled vehicle 2400, and the like.

[0220] Fig.15E An example of an electric bicycle using a secondary battery of one embodiment of the present invention is shown. An electric bicycle 2500 includes a battery pack 2502. The battery pack 2502 includes an all-solid-state secondary battery of one embodiment of the present invention.

[0221] The battery pack 2502 supplies power to the motor that assists the rider. The battery pack 2502 can be removed from the bicycle 2500 and carried. In addition, the battery pack 2502 and the electric bicycle 2500 may have a display unit that can display the remaining power and the like.

[0222] In addition, if Fig.16A As shown, a secondary battery module 2602 including a plurality of secondary batteries 2601 according to one embodiment of the present invention can be mounted on a hybrid electric vehicle (HEV), an electric vehicle (EV), a plug-in hybrid electric vehicle (PHEV), or other electronic devices.

[0223] Fig. 16B An example of a vehicle having a secondary battery module 2602 is shown. Vehicle 2603 is an electric vehicle that uses an electric motor as a power source for traveling. Alternatively, vehicle 2603 is a hybrid vehicle that can appropriately select an electric motor and an engine as a power source for traveling. By using one embodiment of the present invention, a vehicle with high safety and long driving distance can be realized.

[0224] The secondary battery can not only drive the motor (not shown), but also supply power to light-emitting devices such as headlights and interior lights. In addition, the secondary battery can supply power to display devices such as speedometers, tachometers, and navigation systems and semiconductor devices that the vehicle 2603 has.

[0225] In the vehicle 2603 , the secondary battery included in the secondary battery module 2602 can be charged by receiving electric power from an external charging device using a plug-in method or a contactless power supply method.

[0226] Fig. 16C The figure shows a case where a vehicle 2603 is charged from a ground-mounted charging device 2604 via a cable. When charging is performed, the charging method or connector specifications can be appropriately performed in accordance with the provisions of CHAdeMO (registered trademark) or the combined charging system "Combined Charging System". For example, by supplying power from the outside using plug-in technology, the secondary battery module 2602 installed in the vehicle 2603 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an AC / DC converter. The charging device 2604 can be as follows: Fig. 16C The illustrated arrangement is in a house, but it could also be a charging station in a commercial facility.

[0227] In addition, although not shown in the figure, it is also possible to install a power receiving device in the vehicle and supply power contactlessly from a power transmission device on the ground for charging. When a contactless power supply method is used, by assembling a power transmission device in a road or an outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the contactless power supply method can also be used to send and receive power between vehicles. Furthermore, a solar cell can be set on the outside of the vehicle to charge the secondary battery when the vehicle is parked or driving. Such contactless power supply can be achieved using an electromagnetic induction method or a magnetic field resonance method.

[0228] Fig. 16C The house shown includes a power storage system 2612 having an all-solid-state secondary battery of one embodiment of the present invention and a solar panel 2610. The power storage system 2612 is electrically connected to the solar panel 2610 through wiring 2611 or the like. In addition, the power storage system 2612 can be electrically connected to a ground-mounted charging device 2604. The power obtained by the solar panel 2610 can be charged to the power storage system 2612. In addition, the power stored in the power storage system 2612 can be charged to the secondary battery module 2602 included in the vehicle 2603 through the charging device 2604.

[0229] The power stored in the power storage system 2612 can also be supplied to other electronic devices in the house. Therefore, even when power cannot be supplied from a commercial power source due to a power outage, the electronic devices can be used by using the power storage system 2612 of one embodiment of the present invention as an uninterruptible power supply.

[0230] This embodiment mode can be used in combination with other embodiment modes as appropriate. [Explanation of symbols]

[0231] 100: secondary battery, 110: positive electrode, 111: positive electrode active material, 113: positive electrode current collector, 114: positive electrode active material layer, 120: solid electrolyte layer, 121: solid electrolyte, 130: negative electrode, 131: negative electrode active material, 133: negative electrode current collector, 134: negative electrode active material layer, 140: substrate, 141: wiring electrode, 142: wiring electrode, 250a: positive electrode, 250b: solid electrolyte layer, 250c: negative electrode, 251: electrode plate, 252: insulating tube, 253 : electrode plate, 261: bottom member, 262: upper member, 264: butterfly nut, 265: O-ring, 266: insulator, 270a: packaging member, 270b: packaging member, 270c: packaging member, 271: external electrode, 272: external electrode, 273a: electrode layer, 273b: electrode layer, 500: secondary battery, 501: positive electrode current collector, 502: positive electrode active material layer, 503: positive electrode, 504: negative electrode current collector, 505: negative electrode active material layer, 506: negative electrode, 50 7: solid electrolyte layer, 509: outer package, 510: positive lead electrode, 511: negative lead electrode, 521: first plate, 524: second plate, 525a: fixing device, 525b: fixing device, 2100: mobile phone, 2101: frame, 2102: display unit, 2103: operation button, 2104: external connection port, 2105: speaker, 2106: microphone, 2107: secondary battery, 2200: electronic cigarette, 2201: heating element, 2202: rod, 2 204: secondary battery, 2300: unmanned aerial vehicle, 2301: secondary battery, 2302: rotor, 2303: camera, 2400: electric two-wheeled vehicle, 2401: secondary battery, 2402: display unit, 2403: handlebar, 2500: bicycle, 2500: electric bicycle, 2502: battery pack, 2601: secondary battery, 2602: secondary battery module, 2603: vehicle, 2604: charging device, 2610: solar panel, 2611: wiring, 2612: power storage system.

Claims

1. A secondary battery comprising: positive electrode; negative electrode; as well as A solid electrolyte layer between the positive electrode and the negative electrode, Wherein, the positive electrode has a crystal structure similar to a CdCl2 type crystal structure.

Citation Information

Patent Citations

  • Lithium secondary battery, manufacturing method of particle for cathode active material coating, and manufacturing method of lithium secondary battery

    JP2008226463A

  • All-solid-state lithium ion secondary battery

    JP2010272344A

  • Composite cathode active material, all-solid battery and manufacturing method for the same

    JP2011233246A